Quantitative risk assessment of human trichinellosis caused by consumption of pork meat sausages in Argentina - Sequeira, Gabriel Jorge; Zbrun, María Virginia; Soto, Lorena Paola; Astesana, Diego Martín; Blajman, Jesica E.; Rosmini, Marcelo Raúl; Frizzo, Laureano Sebastian; Signorini, Marcelo (Wiley, 2019)
In Argentina, there are three known species of genus Trichinella; however, Trichinella spiralis is most commonly associated with domestic pigs and it is recognized as the main cause of human trichinellosis by the consumption of products made with raw or insufficiently cooked pork meat. In some areas of Argentina, this disease is endemic and it is thus necessary to develop a more effective programme of prevention and control. Here, we developed a quantitative risk assessment of human trichinellosis following pork meat sausage consumption, which may be used to identify the stages with greater impact on the probability of acquiring the disease. The quantitative model was designed to describe the conditions in which the meat is produced, processed, transported, stored, sold and consumed in Argentina. The model predicted a risk of human trichinellosis of 4.88 × 10−6 and an estimated annual number of trichinellosis cases of 109. The risk of human trichinellosis was sensitive to the number of Trichinella larvae that effectively survived the storage period (r = 0.89), the average probability of infection (PPinf) (r = 0.44) and the storage time (Storage) (r = 0.08). This model allowed assessing the impact of different factors influencing the risk of acquiring trichinellosis. The model may thus help to select possible strategies to reduce the risk in the chain of by‐products of pork production.